Internal Medicine Residents’ Perceptions of Point-of-Care Ultrasound in Residency Program: Highlighting the Unmet Needs - Martha Rosana; Oke Dimas Asmara; Rabbinu Rangga Pribadi; Kemal Fariz Kalista; Kuntjoro Harimurti (Acta Medica Indonesiana)
Background: Point-of-care ultrasound (POCUS) is increasingly used in internal medicine   field. Ultrasound training has been part of the training provided in the Internal Medicine Residency Program (IMRP). The aim of this study is to examine the residents’ needs and perceptions regarding their competency and needs of POCUS. Methods: We conducted a cross-sectional descriptive study using secondary data from a survey  among internal medicine residents at the Faculty of Medicine Universitas Indonesia, Cipto Mangunkusumo National General Hospital. The survey was conducted to evaluate and improve the curriculum in IMRP. Results: A total of 175 out of 197 residents (88.8%) completed the questionnaire. Almost all the residents (99.4%) agreed that POCUS is a beneficial must-have skill during residency. Nevertheless, only 40% of residents identified themselves as competent in POCUS. Sixty-two percent residents reckoned that the training received during the residency program is insufficient. They indicated that the most useful skills are US of hepatobiliary, lungs, heart, kidneys, and US-guided procedures. Conclusion: This study confirms that there is a need for POCUS training for   IM residents, as the majority perceived themselves as unable to perform US. It is necessary to optimize the training provided to ensure proficiency.